Role of Imaging in the COVID-19 Pandemic - Kohli, Anirudh (Indographics, 2022)
In the last 2 years, we have seen the most unprecedented times of our lives. The pandemic appears to be petering off and hopefully will become endemic. These 2 years have been a significant learning experience with many new imaging techniques, medical and social concepts introduced. Also, along the pandemic course, numerous articles and editorials were penned on new learnings, as well as new thoughts on controlling and mitigating the suffering of those afflicted. From a collection of editorials and articles in The Indian Journal of Radiology and Imaging (IJRI) on the pandemic, this review is constructed to put imaging-related facts in a perspective.1234567891011 Even though the pandemic may have petered off, this will serve as a memory, as well as repository of information for future pandemics.
Keywords: COVID-19 pandemic; radiology; imaging; HRCT